Enhancing Students' Critical Thinking Skill Through STEM-Oriented PJBL with Mind Mapping Support on Cardiovascular System Material - Ayu Riski Aulia; Khairuna Khairuna (Universitas Labuhanbatu, 2025)
Background: this study is the low critical thinking skills of students and the limited learning models that can stimulate it optimally. This study aims to analyse the effect of STEM-based Project-Based Learning (PjBL) learning model assisted by mind mapping on students' critical thinking skills on cardiovascular system material. Methodology: This research used quasi-experimental method with research design using Pretest Postest Control Group Design. The research sample was XI MIPA class students with the experimental class getting the STEM-based PjBL model treatment assisted by mind mapping, and the control class using conventional learning. The research instrument was a critical thinking skills test based on indicators from Facione (2013). Data were analysed using normality test, homogeneity test, and F test (ANOVA) with 5% significance level. Findings: The results showed that there was a significant effect of 0.000, meaning that there was a significant difference between the experimental group and the control group simultaneously on students' critical thinking skills after the application of the STEM-based PjBL model assisted by mind mapping. Students in the experimental class showed an increase in the ability to interpret, analyse, evaluate, and draw conclusions from the Cardiovascular system material. Contribution: These findings suggest that the integration of project-based learning with STEM approach and visualisation through mind mapping is effective in improving students' higher order thinking skills in a meaningful way.